Prophylactic Midface Lift in Midfacial Trauma - Brown, Ryan; Lozada, Kirk; Kadakia, Sameep; Gordin, Eli; Ducic, Yadranko (Facial Plastic Surgery, 2017)
The objective was to review our favorable experience in the use of prophylactic midface lifts in the setting of severe midfacial trauma. A retrospective review of a consecutive series of patients undergoing prophylactic midface lifts at the time of definitive fracture repair in a County Hospital Level 1 trauma center was done. All patients undergoing midface lifts at the time of fracture repair by the senior author from July 1998 to July 2012 were included in this review. A total of 72 patients (58 males, 14 females, average age: 36.2 years) were available for review. Sixty-three patients had a minimal follow-up of at least 3 months. No complications felt to be related to the midfacial suspension were noted. There were no instances of frontal nerve paralysis or palsy. There were no patients with ectropion. Patient midfacial symmetry was evaluated by two blinded facial plastic surgeons. It was felt to be excellent in 53 patients, good in 9, fair in 1, and poor in none. The force of trauma necessary to elicit a severe midfacial fracture and the subsequent subperiosteal dissection required to expose the fractures for rigid fixation result in severe laxity of the midfacial soft tissue envelope. Failure to suspend and support these soft tissues will result in significant facial asymmetry. Prophylactic endoscopic midface suspension appears to be a safe and effective method of largely eliminating this problem and should be considered in the setting of severe midfacial fractures.
Keywords: midface lift; maxilla fractures; facial trauma; facial deformity; endoscopic surgery